Pemilihan Tempat Persalinan dan Faktor yang Berhubungan - Dewi Nopiska Lilis; Yuli Suryanti; Tiurlan Sirait (Jurnal Kesehatan Komunitas, 2022)
Data on deliveries in 2020 in the working area of ​​the Muara Kumpeh Health Center, there are still deliveries carried out at home, this is contrary to the Minister of Health Regulation No. 97 of 2014. The purpose of this study was to determine the description of the choice of place of delivery which was influenced by the respondent's knowledge and other factors, namely education, socio-culture, community commitment, and family support. This study aims to determine the factors associated with the choice of place of delivery. This type of research is quantitative with a retrospective design. The populations in this study were mothers who had given birth from January to December 2020. The sample was selected using the Proportional Simple Random Sampling technique using the Slovin formula for as many as 86 respondents, which was carried out from May 2021 to August 2021 by filling out questionnaires, using univariate and bivariate analysis with Chi-Square statistical test. The results showed that 52.3% of respondents chose to give birth in a health facility, respondents who had good knowledge 41.9%, respondents who had higher education 62.8%, respondents who were still influenced by culture 51.2%, respondents who had a high commitment 54,7%, and respondents who expressed support regarding the choice of place of delivery were 51.2%. Statistical analysis showed that the variabels that were significantly related to the choice of place of delivery were knowledge, education, socio-culture, community commitment, and family support with a p-value (0.000) <0.05. It is hoped that this research will become input, information, and evaluation for midwives in the working area of ​​the Muara Kumpeh Health Center, the need to increase socialization to the community so that they have knowledge and initiative, and the need for cross-sectoral collaboration to support community commitment to childbirth in health facilities.